Fabrication Of Three Dimensional (3d)-Printed Electrodes-Based Thermoplastic Carbon Nanomaterials For Electrochemical Breast Cancer Dna Biosensor - Omar, Muhamad Huzaifah (2023)
Three-dimensional (3D) printing or additive manufacturing is a promising technology to revolutionise traditional manufacturing methods. Nowadays, numerous studies have utilised 3D printing technology to replace conventional electrodes in the fabrication of electrochemical sensors and biosensors due to its low cost, rapid prototyping, and flexibility in design. The main aim of this study is to explore the 3D-printed electrode’s potential as an electrochemical biosensor for breast cancer gene (BRCA1) detection. The first section focuses on the electrochemical performances of 3D-printed polylactic acid/carbon fiber (PLA/CF) electrodes. A novel electrochemical treatment using the differential pulse voltammetry (DPV) technique in hexaammineruthenium (III) chloride (RuHex) solution is proposed. Electrochemical characterisations revealed that the DPV-RuHex electrochemical treatment significantly improved the electrochemical performance of the 3D PLA/CF electrode. Furthermore, field emission scanning electron microscopy (FESEM) micrographs demonstrated that more PLA layers degraded after the treatment, which increased the electrode’s electroactive surface area. The second part investigates the effect of DPV treatment in RuHex and sodium hydroxide (NaOH) solutions on the 3D-printed PLA/graphene (PLA/G) electrode. The electrochemical analyses revealed no significant difference between the two treatments.